THE ROLE OF EXCHANGE TRADED FUND TO DRIVE THE GROWTH OF THE MUTUAL FUND INDUSTRY IN THE CAPITAL MARKET ACCORDING TO A REVIEW OF ISLAMIC LAW - Bakhri, Syaeful; Rana, Mohammad; Pradini, Anez Yuniar (AT-TIJARAH: Jurnal Penelitian Keuangan dan Perbankan Syariah, 2021)
As a product that has just been listed on the stock exchange, this Exchange Traded Fund (ETF) has attracted the attention of various lines of capital market investors. ETF is known as one of the mutual fund product innovations as a follow-up to POJK No. 49/POJK.04/2015. This study is a descriptive study of this product with all the features and advantages and uniqueness it has as a form of diversification of existing mutual fund products. This study also seeks to explore the strengths and weaknesses of ETFs both internally and externally. Interestingly, this descriptive study presents data on investor enthusiasm for ETF products. One of the main attractions of this product is that apart from being traded on the stock exchange, the price is also very cheap. Not only explaining in terms of products and their uniqueness, but this study also discusses the review of Islamic law on ETF transactions on the stock exchange. When compared with the practice of buying and selling, there are many similarities. And there are several other interesting factors to observe regarding the considerations of investors in choosing mutual fund instruments, especially ETFs as an alternative to new investments in the capital market.